Influence of Selected Demographic Variables on the Development and Transfer of Life Skills: A Survey of Higher Education Institutions of Khyber Pakhtunkhwa Pakistan - Dr. Wasim Khan; Mohib Ur Rehman; Muhammad Fehmeed; Ishfaq Ali; Bilal Ahmad; Syed Muhammad Ishaq; Khalid Usman (Al-Qanṭara, 2023)
The present study was conducted for two important purposes; a) determining the influence of demographic variables such as gender and formats of sports in the development of selected life skills (i.e., Decision-making skills, interpersonal communication skills, and identity development skills), and b) determining the influence of demographic variables in transferring these skills to other domains of life (family, academic and community endeavors) among university students of Khyber Pakhtunkhwa (KP), Pakistan. Method: A total of 389 questionnaires were distributed among the participants, out of which 335 (88.11%) received back. As the study was guided by a descriptive model from quantitative research method, therefore, a structured questionnaire was developed and used for collecting the requisite data. The responses were tabulated and analyzed with the help of computer software. In addition to descriptive statistics like frequency and percentage that is used to describe the basic features about the samples and the measures, some other statistical test like, Independent Sample t-Test were used to taste the set hypotheses of the study. Findings: The result showed that Male reported higher mean score on various dimensions of life skills development through sport compared with their counter-parts female athletes (p < .05) and no statistically significant differences were noted in transferring life skills to other domains of life (p > .05). Likewise, the analyzed data revealed that team sport-participants reported higher mean score on life skills development compared with individual sport-participants (p < .05) and no statistically significant differences were noted in transferring life skills to other domains of life (p > .05). Implications: The sport participation among female can be increased by projecting the importance of life skills development and their transfer through sport, especially in conservative societies like Pakistan, where religious obligations are dominant over culture. The integrative force of sport towards life skills development may be utilized in a befitting manner by the people in the field of Sport Sciences and Physical Education in Pakistan. Keywords: Gender, Formats of Sport, Development, Transfer & Life Skills